(untitled) (Research, Society and Development, 2022)
Among the outstanding vegetables is the genus Capsicum belonging to the Solanaceae family, which involves peppers (Capsicum spp.) and bell peppers (Capsicum annum). The fruits of C. chinense are characterized by a great diversity in terms of colors, shapes and pungency, which can range from mild to extremely pungent. The objective of this work was to evaluate the development of seedlings of Capsicum spp. grown in different types of substrate. The experiment was carried out in the Experimental Sector of Agronomy of the Centro Universitário Tocantinense Presidente Antônio Carlos in Araguaína -TO from July 27 to August 28, 2022. The varieties of Bhut Jolokia and Biquinho Vermelha were sown in polyethylene tubes and at 31 DAS were evaluated: plant length, root system length, stem diameter and number of leaves. The organic substrates evaluated showed good results in the development of seedlings of Capsicum spp., this indicates that instead of being discarded, they can be used in sowing.